On the Finitary Bisimulation - Aceto, Luca; Ingólfsdóttir, Anna (BRICS Report Series, 1995)
The finitely observable, or finitary, part of bisimulation is a key tool in establishing full abstraction results for denotational semantics for process algebras with respect to bisimulation-based preorders. A bisimulation-like characterization of this relation for arbitrary transition systems is given, relying on Abramsky’s characterization in terms of the finitary domain logic. More informative behavioural, observation-independent characterizations of the finitary bisimulation are also offered for several interesting classes of transition systems. These include transition systems with countable action sets, those that have bounded convergent sort and the sort-finite ones. The result for sort-finite transition systems sharpens a previous behavioural characterization of the finitary bisimulation for this class of structures given by Abramsky. AMS Subject Classification (1991): 68Q10 (Modes of computation), 68Q55 (Semantics), 03B70 (Logic of Programming), 68Q90 (Transition nets). Keywords and Phrases: Concurrency, labelled transition systems with divergence, bisimulation preorder, finitary relations, domain logic for transition systems.